The Impact of social media on Adolescents' Concepts of Beauty and Its Reflections on Their Mental Health - Nihed Bouzeghaya (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2026)
This study investigates the impact of social media use on shaping unrealistic aesthetic perceptions among adolescents, revealing the repercussions of these perceptions on their mental health. Applying a mixed-methods approach to a purposive sample (n=60), and relying on (BSMAS, SATAQ-4, GHQ-28) scales supported by content analysis of interviews and adolescents' posts on their pages; the results showed a strong positive correlation between intensity of use and adoption of those false standards (r=0.72), met by a clear negative impact on mental health (r=-0.65). The qualitative analysis also revealed that 75% of the content published or followed by adolescents promotes an artificial body ideal, leading to appearance dissatisfaction among 70% of the participants. The study concludes the necessity of activating media literacy programs and guidance intervention to promote self-acceptance.